2000
DOI: 10.1016/s0924-9338(00)00226-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical variables in subjects with adjustment disorder after suicide attempts

Abstract: The investigation of biological correlates of suicidal behavior is important for identifying high-risk subjects. The objective of this study was to examine the neurochemical variables' platelet MAO activity and urinary MHPG, 5HIAA and HVA, the main metabolites of noradrenaline, serotonin and dopamine, neurotransmitters that are considered to be involved in the pathophysiology of suicidal behavior, as well as plasma cortisol, in a group of subjects with adjustment disorder after a suicide attempt. Fifty-three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…However, many studies of HPA axis function in bipolar disorder have not examined the potential effects of Suicidal Behavior (SB) (Cassidy et al, 1998;Cervantes et al, 2001;Cookson et al, 1985;Godwin, 1984;Linkowski et al, 1994;Rybakowski and Twardowska, 1999;Schmider et al, 1995) and studies of the association between HPA axis activity and suicidal behavior in varied diagnostic groups have had mixed results (Black et al, 2002;Coryell and Schlesser, 2001;Dahl et al, 1991;Duval et al, 2001;Jokinen and Nordström, 2008;Lindqvist et al, 2008;Pfennig et al, 2005;Pitchot et al, 2008;Tripodianakis et al, 2000;Yerevanian et al, 2004;Kamali et al, 2012).…”
Section: Risk Factors Associated With Biological Componentsmentioning
confidence: 99%
“…However, many studies of HPA axis function in bipolar disorder have not examined the potential effects of Suicidal Behavior (SB) (Cassidy et al, 1998;Cervantes et al, 2001;Cookson et al, 1985;Godwin, 1984;Linkowski et al, 1994;Rybakowski and Twardowska, 1999;Schmider et al, 1995) and studies of the association between HPA axis activity and suicidal behavior in varied diagnostic groups have had mixed results (Black et al, 2002;Coryell and Schlesser, 2001;Dahl et al, 1991;Duval et al, 2001;Jokinen and Nordström, 2008;Lindqvist et al, 2008;Pfennig et al, 2005;Pitchot et al, 2008;Tripodianakis et al, 2000;Yerevanian et al, 2004;Kamali et al, 2012).…”
Section: Risk Factors Associated With Biological Componentsmentioning
confidence: 99%
“…The suicidal process among patients in this diagnostic group is shorter and more rapidly evolving compared to patients with MDD (Polyakova, Knobler, Ambrumova et al, 1998), and there are often no indications of emotional or behavioral issues during early adolescence in suicide victims diagnosed with AD (Portzky, Audenaert, & van Heeringen, 2005). Tripodianakis, Markianos, Sarantidis et al (2000) investigated neurochemical characteristics in patients diagnosed with AD after a suicide attempt, and found higher concentrations of cortisol in plasma, compared with healthy controls. Our research group recently reported lower orexin levels in cerebrospinal fluid of suicide attempters with MDD compared to AD, suggesting a hypothalamic neurobiological distinction between the two diagnostic groups (Brundin, Björkqvist, Petersén et al, 2007).…”
Section: The Time-course Of Illness and Hpa-axis Disturbancesmentioning
confidence: 99%
“…Elevated cortisol levels are found in individuals with depression or adjustment disorder and a history of suicide attempts, compared to healthy controls (Dahl et al, 1991; Tripodianakis et al, 2000). Association between DST non-suppression and future suicide attempts and completions was reported in a meta-analysis of eleven studies (Lester, 1992) and also in several subsequent studies (Coryell and Schlesser, 2001; Jokinen and Nordström, 2008, 2009; Jokinen et al, 2009; Yerevanian et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…However, many studies of HPA axis function in bipolar disorder have not examined the potential effects of suicidal behavior (Cassidy et al, 1998; Cervantes et al, 2001; Cookson et al, 1985; Godwin, 1984; Linkowski et al, 1994; Rybakowski and Twardowska, 1999; Schmider et al, 1995) and studies of the association between HPA axis activity and suicidal behavior in varied diagnostic groups have had mixed results (Black et al, 2002; Coryell and Schlesser, 2001; Dahl et al, 1991; Duval et al, 2001; Jokinen and Nordström, 2008, 2009; Lindqvist et al, 2008; Pfennig et al, 2005; Pitchot et al, 2008; Tripodianakis et al, 2000; Yerevanian et al, 2004). …”
Section: Introductionmentioning
confidence: 99%